THE MEANING OF MANGGAN NANTAUW TRADITION IN PEOPLE AROUND BUKIT PULAI KERINCI REGENCY JAMBI PROVINCE - Prasiska, Rici (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
Manggan Nantauw tradition is a tradition held by local people in Bukit Pulai to celebrate their women’s pregnant. This tradition has a process which has several steps to do. This research is aimed to see the process of Manggan Nantauw tradition, to find the meaning behind this tradition, and to know the reason of the existence of Manggan Nantauw tradition around people in Bukit Pulai. This research used ethnography which is one of types of qualitative research. The data of this research were taken in Bukit Pulai at Kerinci regency, Jambi province. The informants of this research were traditional leaders, whole family and people that do Manggan Nantauw tradition. The techniques of data collection of this research were close interview, documentation and field observation. Furthermore, to analyze the data, it was using 12 steps from Spradley analysis which were corresponded to the situation in the field. The result of the research shows Manggan Nantauw tradition still exists in Bukit Pulai people’s life. The meaning of this tradition can be seen from its process. It has meaning in each used tools such as a mat for born baby, a cattle, two glasses, two plates, a wide plate, two rice bowls, two spices bowls, two big spoons, two small spoons and two washing hand bowls. The other is meaning from its materials such as areca, gambir, leaf cigarette, rice, curry and chickens. The reason why Bukit Pulai people still do this tradition is because this is in line with Islamic belief and one of ancient cultural heritages that give good effect for the society which it can tighten familiarity among the people. Manggan Nantauw tradition must be maintained and preserved. For the local people, they should keep the existence of this tradition. Kerinci government also has to give support toward the preservation of this tradition as one of characteristics of Kerinci people especially Bukit Pulai people.